Divine Love and Sincere Devotion in the Mystical Poetry of Rabi’ah al-Adawiyah - Salwa Rismilillah Akmalia; R. M. Nur Sakinah (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2025)
This paper examines the concept of mahabbah lillah (divine love) in the poetry of Rabi’ah al-Adawiyyah from a literary perspective, drawing on biographical and cultural contexts. As an 8th-century female Sufi figure, Rabi’ah is known for her sincere love for God—motivated neither by fear of Hell nor desire for Paradise, but by pure devotion. The study analyzes ten selected poems that express themes of sacred love, spiritual longing, and total surrender. The findings reveal that her poetry not only possesses literary value but also holds deep spiritual significance within the early Islamic tradition. Her work demonstrates how literature can become a powerful medium for expressing inner experiences and the human relationship with the Divine.